From Pailis to pasungko negotiating the present, ascertaining the future (indigenous knowledge systems and opportunities for biodiversity management and conservation) - Castro, Luz C. Sevidal (Langkit : the Official journal of the College of Arts & Social Sciences Mindanao State University-Iligan Institute of Technology, 2006)
This study describes the indigenous knowledge systems, the adaptive strategies, and the traditional resource use practices of the Subanun in Mt. Malindang. The study sites included six (6) communities located in the province of Misamis Occidental. It benefited from a triangulation of methods and sources: documentary review and secondary data gathering: focus group discussion; key informant interviews and testimonies, participant and non-participant observation.